Development of dehydrated candied roselle (Hibiscus sabdariffa) - Valila, Nympha V.
Fresh, mature roselle calyces were transported from Gapan, Nueva Ecija and stored at 20°F for the duration of the study. A four-phase study was done to develop a sweet-salty flavored dehydrated product from the calyces. A better method of syruping between boiling in 40°Brix and soaking in 40°Brix overnight was initially determined. This was followed by the determination of the optimum concentration of syruping prior to drying. The effect of salting on product quality was studied by adding salting as a procedure before syruping. The optimum brine concentration to be used was also determined. Subjective tests were done in each phase by presenting the products to a panel of 10 members for evaluation of the color, texture, flavor and acceptability. the products from each phase were analyzed for moisture content, pH, ascorbic acid content, microbiological quality and color retention. From the results of these subjective and objective tests, a standardized procedure was obtained for the processing of the roselle calyx into a dehydrated candied product. the calyces were soaked in 60°Salometer brine for 2 hrs., washe and then drained. It was then boiled for 10 mi. in 50°Brix syrup and then dehydrated in acabinet dryer witha relative humidity of 51%, and at 100-200°F for 80 min.